Vizualne in avditivne reprezentacije prostora in mrežnega prostora - Jauk, Werner (Muzikološki zbornik, 2007)
The use of the term space in net-space is based on a mechanistic point of view, an imagery of visual space out of bodily experience of the world. By technical turns the active interaction to explore space more and more becomes a passive one. This is where the auditory space comes in and serves as an imagery for net-space. An experiment proved an auditory imagery just evoked by different sharpness/pitch. Subjects were instructed to show the point in space where they imagined a sound with a specific timbre is located. The results show two groups of subjects: a visual type that imagines space by his own movement and an exploring auditory type which imagines space according to the internalized knowledge of the behavior of sound: dull sounds are far away,sharp sounds are near. Pitch revealed a significant effect on the synesthetic imagination on the Y-axis. The secondary interpretation of sound as space-localization indicates auditory-space to be a space of occurrences and supports McLuhans assumption of an analogy of "ear and electricity", of auditory space and electric space, nowadays net-space. Despite the metaphoric use of space artistic experiments initiate auditory-space-imagery to use it as a psychological interface to the net-space, another space of occurrences defined by communication processes.
Keywords: glasba; glasbeni prostor; kognitivni prikaz (avditivnega) prostora; mrežni prostor; music; prostorsko zaznavanje